2018
DOI: 10.1088/1361-6463/aabd68
|View full text |Cite
|
Sign up to set email alerts
|

Theory of spin and lattice wave dynamics excited by focused laser pulses

Abstract: We develop a theory of the spin wave dynamics excited by ultrafast focused laser pulses in a magnetic film. We take into account both volume and surface spin wave modes in the presence of applied, dipolar and magnetic anisotropy fields and include the dependence on laser spot exposure size and magnetic damping. We show that the sound waves generated by local heating by an ultrafast focused laser pulse can excite a wide spectrum of spin waves (on top of a dominant magnon-phonon contribution). Good agreement wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Brillouin light scattering spectroscopy experiments have previously shown that the thermalisation of an overpopulated magnon gas, in combination with magnon-phonon scattering, leads to the self-organisation of so-called magnetoelastic bosons at the crossing point of the magnon and phonon dispersions 15 . This accumulation phenomenon is confirmed by micromagnetic simulations taking into account the magnetoelastic interaction of magnon-polaron dynamics 16 . Calculations of spin pumping by a parametric excitation also prove that magnons are resonantly enhanced in strength at the magnetoelastic crossing point 30 .…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Brillouin light scattering spectroscopy experiments have previously shown that the thermalisation of an overpopulated magnon gas, in combination with magnon-phonon scattering, leads to the self-organisation of so-called magnetoelastic bosons at the crossing point of the magnon and phonon dispersions 15 . This accumulation phenomenon is confirmed by micromagnetic simulations taking into account the magnetoelastic interaction of magnon-polaron dynamics 16 . Calculations of spin pumping by a parametric excitation also prove that magnons are resonantly enhanced in strength at the magnetoelastic crossing point 30 .…”
Section: Resultssupporting
confidence: 52%
“…It is well understood that a spatially-localised perturbation creates propagating waves with wave vectors determined by the profile of the excitation 16 , 22 . The results shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This accumulation phenomenon is confirmed by micromagnetic simulations, taking into account the magnetoelastic interaction of magnonpolaron dynamics in Ref. [16]. Calculations of spin pumping by a parametric excitation also prove that magnons are resonantly enhanced in strength at the magnetoelastic crossing point [30].…”
supporting
confidence: 54%
“…The large-amplitude precessional motion leads to strong instability of the spin system and generates a sizeable number of spin waves, strongly populating the low-energy part of the magnon spectrum. The subsequent repopulation in the presence of a magneto-elastic interaction leads to effective 'condensation' of the waves into the magnon-polaron part of the spectrum, observed both experimentally and in micromagnetic simulations [15,16]. Ultimately, these magnon-polaron waves synchronize and achieve such high amplitude that they induce complete switching of magnetisation at the wave maxima.…”
mentioning
confidence: 96%
“…( 3). extension of Damon-Eshbach theory into AFM also gives the spatial profiles of the mode-dependent magnetization dynamics [37,38]. In Fig.…”
mentioning
confidence: 99%